Phantoms à base de PVCP para simular imagens ultrassonográficas de lesões de mama - Souza, Andréa Farias de (2017)
Breast cancer is the second most common type of cancer affecting women in the world. An early and fast diagnosis is necessary for a specialized care of the cases. This study aims to elucidate a protocol on phantom manufacturing containing qualitative features simulating breast cancer. This new procedure was based on a previously protocol made by our team, published on Carvalho et al. 2016. Here were reproduced 21 types of lesions-like structures and compared them with ultrasound images from an image bank and evaluated by a specialist. The qualitative features of the ultrasound images were correlated with the materials used and their effects produced. The encapsulated lesions and internal content with low attenuation presented qualitative features similar to benign lesions, (regular, anechoic and acoustic reinforcement). Lesions without capsule and high concentrations of scatterers show malignant lesions images features (irregular, hypoechoic and enhanced sound transmission). Features that distinguish benign and malignant lesions could be reproduced and therefore these phantoms can be used in training medical staff and develop lesion classification software.